Microbial soft rot of cultivated fruits and vegetables - Nadine Chahrazade, Djellout (Algerian Journal of Biosciences, 2020)
The nutritional richness of fruits and vegetables makes them an ideal target for microorganisms, causing in particular soft rot. The microorganisms responsible for this pathology are generally found in the environment, and are endowed with a very important enzymological power, the main action of their pathogenicity. These enzymes, which allow the degradation of the plant cell wall, allow them to cross the protective wall of the plant, causing a liquefaction of tissues, whose environmental conditions as well as transport and storage conditions favour the development of these phytopathogens. A better understanding of spoilage microorganisms and the characteristics of spoilage should allow the development of new conservation and protection technologies and reduce the loss of vegetables due to spoilage. This review summarizes the main literature data on soft rot, and the diversity and mode of action of the main microbial causal agents.